The gastrointestinal tract in hunger and satiety signalling. Issue 6 (21st June 2021) - Tack, Jan; Verbeure, Wout; Mori, Hideki; Schol, Jolien; Van den Houte, Karen; Huang, I‐Hsuan; Balsiger, Lukas; Broeders, Bert; Colomier, Esther; Scarpellini, Emidio; Carbone, Florencia
Abstract: Background: Different peripheral pathways are implicated in the regulation of the food ingestion‐digestion cycle. Methods: Narrative review on gastrointestinal mechanisms involved in satiety and hunger signalling. Results: Combined mechano‐ and chemoreceptors, peripherally released peptide hormones and neural pathways provide feedback to the brain to determine sensations of hunger (increase energy intake) or satiation (cessation of energy intake) and regulate the human metabolism. The gastric accommodation reflex, which consists of a transient relaxation of the proximal stomach during food intake, has been identified as a major determinant of meal volume, through activation of tension‐sensitive gastric mechanoreceptors. Motilin, whose release is the trigger of gastric Phase 3, has been identified as the major determinant of return of hunger after a meal. In addition, the release of several peptide hormones such as glucagon‐like peptide 1 (GLP‐1), cholecystokinin as well as motilin and ghrelin contributes to gut‐brain signalling with relevance to control of hunger and satiety. A number of nutrients, such as bitter tastants, as well as pharmacological agents, such as endocannabinoid receptor antagonists and GLP‐1 analogues act on these pathways to influence hunger, satiation and food intake. Conclusion: Gastrointestinal mechanisms such as gastric accommodation and motilin release are key determinants of satiety and hunger. Abstract :